The Invader of Bosnia and His Family. Duke Coloman of Slavonia in the Realm of His Father and Brother - Barabás, Gábor (Historical Thought, 2025)
The paper focuses on the Hungarian royal family in the early thirteenth century. The aim of this analysis is to illustrate the relations between the monarch, Andrew II (1205–1235), and his sons, that can be described as quite extraordinary, as not only the oldest brother, the future King Béla IV (1235–1270), but also the second son, Prince Coloman, was crowned king around 1214 in course of the Hungarian expansion in the Principality of Galicia. Relation between Béla and Coloman remained cordial until the end, even after the former ascended the throne.